DINAMIKA PENGANGGURAN DAN LOWONGAN PEKERJAAN DI PROVINSI BANTEN - Suwarto, Suwarto; Ridwan, Mukhsin; Nurfian, Ani (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
Unemployment refers to the state where individuals within the labor force are either unemployed or actively seeking employment. This study examines the dynamics of unemployment and job availability in Banten Province from 2021 to 2023, using data from the Central Bureau of Statistics (BPS). The research employs a quantitative descriptive method, analyzing the Open Unemployment Rate (OUR) by regency/city and age group, the workforce based on education level, and job vacancies by gender and region. The results indicate that Banten Province's OUR reached 8.20%, with Serang Regency contributing the highest rate at 10.38%. The 15-19 age group recorded the highest unemployment rate at 40.59%. Job vacancies totaled only 51,163, far below the demand, resulting in a deficit of 459,680. These findings highlight significant challenges in meeting the employment needs of the region. This study is expected to contribute to resolving unemployment issues and fostering equitable economic development in Banten Province.